A study on prognostic significance of serum uric acid in acute myocardial infarction in a tertiary care institute - Biswas, Kaushik; Halder, Subrata; Sarkar, Ramita; Roy, Koushik (International Journal of Research in Medical Sciences, 2016)
Background: This study was done to find out any relationship between serum uric acid and AMI severity and its short-term outcome. To see the correlation between serums uric acid level with Killip Class and mortality outcome following AMI. Methods: 100 patients of AMI were included this study based on the inclusion and exclusion criteria. Detailed history, physical examination and relevant systemic examination including detailed examination of CVS system were done as per a structured proforma and necessary laboratory investigations were done. Results: 100 cases of myocardial infarction were studied, out of which 90 patients had STEMI and 10 patients had NSTEMI. There is significant difference of D0 uric acid level was observed for previous history of AMI. There is significant difference in mean uric acid level between dyslipidemic and non-dyslipidemic population. There is significant difference in mean uric acid level on D0 between diabetic and non-diabetic population. Serum uric acid level is low among patients with lower Killip class and high among higher Killip class. Lower the uric acid level, higher the percentage of survival and higher the uric acid level, higher the percentage of mortality. Conclusions: Patients of Killip class lll and lV had higher levels of uric acid as compared to patients of class l and ll. Combination of Killip class and serum uric acid level after acute myocardial infarction is a good predictor of severity of heart failure after AMI.